The Influence of Leadership, Work Environment, Motivation, Communication, and Training on Employee Performance at PT XYZ – ABC Airport - Astiana Nengsi; Aris Setiyani; Nunung Ayu Sofiati (Dinasti Publisher, 2025)
This study aims to analyze the influence of leadership, work environment, work motivation, organizational communication, and training on employee performance at PT XYZ, ABC International Airport. As a strategic national sector, the aviation industry demands effective human resource management to ensure service excellence and organizational competitiveness. This research employs a quantitative approach with descriptive and verificative methods, using Structural Equation Modeling (SEM) AMOS involving 155 respondents. The analysis results indicate that only organizational communication positively and significantly affects employee performance (p < 0.05), while leadership, work environment, motivation, and training show no direct significant effect. These findings highlight the critical role of effective internal communication in enhancing performance within complex and dynamic work environments such as airports. The managerial implication is the need for the company to prioritize the development of robust internal communication systems both vertically and horizontally to support efficient coordination, prompt decision-making, and overall productivity improvement. This study contributes both theoretically and practically to the development of human resource strategies in the air transportation service sector.